TRANSLANGUAGING AS CHALLENGE AND SUPPORT: VOCATIONAL ESP STUDENTS' EXPERIENCES IN INDONESIAN HIGHER EDUCATION - Marlia Marlia; Muhammad Basri; Sahril Sahril; Ferawaty Syam; Andi Adisaturrahimi (University of Kuningan, 2026)
Translanguaging has received growing attention in multilingual education; nonetheless, its pedagogical implications in English for Specific Purposes (ESP) within vocational higher education are still inadequately examined, especially in Global South contexts. This study, guided by Sanford’s Challenge and Support Theory, examines vocational students' perceptions of Translanguaging techniques as both educational tools and possible limitations in English for Specific Purposes (ESP) classrooms. A qualitative descriptive design was utilized to conduct semi-structured interviews with twenty-one vocational undergraduates participating in ESP courses at an Indonesian higher education institution. Thematic analysis was employed to examine data for recurring patterns of challenge, support, and pedagogical balance. The results indicate that Translanguaging functions as a dual-purpose educational strategy. It offers cognitive support that enhances understanding of subject-specific concepts, alleviates linguistic anxiety, and promotes classroom engagement. Conversely, students indicated that unregulated or excessive use of their first language could limit exposure to English, impede language processing, and obstruct the development of communicative autonomy. Students underscored the significance of instructional mediation, asserting that Translanguaging is most advantageous when utilized as a temporary aid rather than a replacement for involvement in the target language. This study enhances Translanguaging scholarship by framing classroom language practices as a dynamic continuum of challenge and support, rather than a binary distinction between L1 and English. The results underscore the necessity for pedagogically refined Translanguaging procedures in vocational English for Specific Purposes contexts, where language accessibility must be balanced with the advancement of professional English skills. Implications are presented for English for Specific Purposes pedagogy, educator decision-making, and multilingual language policy in vocational higher education.